2023
DOI: 10.1108/dlp-09-2022-0073
|View full text |Cite
|
Sign up to set email alerts
|

Do students look for information differently? Information-seeking behavior during the COVID-19 pandemic

Abstract: Purpose The purpose of this study is to explore the COVID-19 information-seeking behavior of the students in a developing country. This study also explores how the use of information sources changes over time by the students of a public university in Bangladesh. Design/methodology/approach An e-mail was sent along with an online questionnaire to 350 students in a public university in Bangladesh. After sending a couple of follow-up e-mails in May and June 2022, we got limited responses. Later in July, we dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Next ECs may not have been able to distribute print materials due to pandemic restrictions. Lesser sustainability reported by this study's students who used social media (μ = 3.46) as their primary source of information in making EC choice contradicts previous studies of [158,370,373] that identified social media as a leading, rich, and interactive communication source, as well as the study of that reveals it as an effective tool in decision making [374].…”
Section: Insights Of Diversity On Sustainability Of Ecscontrasting
confidence: 99%
“…Next ECs may not have been able to distribute print materials due to pandemic restrictions. Lesser sustainability reported by this study's students who used social media (μ = 3.46) as their primary source of information in making EC choice contradicts previous studies of [158,370,373] that identified social media as a leading, rich, and interactive communication source, as well as the study of that reveals it as an effective tool in decision making [374].…”
Section: Insights Of Diversity On Sustainability Of Ecscontrasting
confidence: 99%
“…The misinformation and disinformation related to public health [ 65 ], particularly in terms of pandemics, where false narratives about the disease and vaccines can cause considerable public health risks [ 66 ], can be minimized using digital health dashboards. The validity of the information can be cited or sourced using trusted external agencies such as the World Health Organization [ 67 ]. Nevertheless, it is difficult to address citizen mistrust in institutions, and the digital dashboards that are built using citizen science [ 3 ], and that operate using anonymized citizen data to generate evidence, can make incremental changes in citizen perception.…”
Section: Discussionmentioning
confidence: 99%
“…Another example comes from Bangladesh. In this country, Tonmoy and Islam (2023) conducted an institutional-based cross-sectional study about information-seeking behavior during the Covid-19 crisis among students ( N = 270) from a public university in Bangladesh. One result that should concern us is that 28.1% of the surveyed students responded “yes” to the statement “information is not available in the native language” (p. 174).…”
Section: Rationale Of the Contextual Factors Examined In The Present ...mentioning
confidence: 99%